Situating the history of science : dialogues with Joseph Needham - Needham, Joseph, 1900-1995.; Habib, S. Irfan; Raina, Dhruv (New Delhi ; New York : Oxford University Press, 1999)
Contributed articles presented at a seminar at New Delhi in Sept. 1996.
Includes bibliographical references and index.
Keywords: Needham, Joseph, -- 1900-1995 -- Congresses; Science -- Historiography -- Congresses